Oncogenic fusion of BCAR4 activates EGFR signaling and is sensitive to dual inhibition of EGFR/HER2 - Bae, Kieun; Kim, Jin Hee; Lee, Ja Young; Kong, Sun-Young; Kim, Yun-Hee; Kim, Sunshin; Yoon, Kyong-Ah (Frontiers in Molecular Biosciences, 2022)
We previously reported CD63-BCAR4 fusion as a novel oncogene that significantly enhanced cell migration and metastasis in lung cancer. To identify effective inhibitors of metastatic activity induced by BCAR4 fusion, we screened a drug library of 381 FDA-approved compounds. The effect of drugs on cell migration was evaluated by monitoring wound healing. Drugs that decreased the cellular mobility of fusion-overexpressing cells compared with that of control cells were selected as candidates. Library screening revealed that erlotinib, canertinib, and lapatinib demonstrated inhibitory effects on cell migration. Activation of the EGFR signaling pathway was detected after ectopic expression of CD63-BCAR4 in normal bronchial epithelial cells, as observed by the increased phosphorylation of tyrosine residues in the EGFR protein. We also confirmed increased levels of the phosphorylated EGFR protein in resected tumors from mice injected with CD63-BCAR4 overexpressing cells. Tyrosine kinase inhibitors (TKIs) of the EGFR family significantly inhibit the migration of BCAR4 fusion-overexpressing cells and induce apoptosis at high concentrations. Among the EGFR family TKIs, canertinib, a dual EGFR/HER2 inhibitor, showed the best inhibitory effect on the migration and viability of BCAR4 fusion-overexpressing cells. We examined the effect of canertinib in vivo using a mouse xenograft model. Oral administration of canertinib to xenografted mice reduced tumor growth induced by the CD63-BCAR4 fusion gene. In addition, canertinib treatment restored E-cadherin expression and reduced the expression of epithelial–mesenchymal transition regulatory factors such as Slug and Snail. Taken together, these results suggest that EGFR/HER2 inhibitors are potential therapeutic options for BCAR4 fusion-harboring lung cancer patients, even in the absence of EGFR mutations.